2020
DOI: 10.1080/00365521.2020.1837927
|View full text |Cite
|
Sign up to set email alerts
|

Lactose after Roux-en-Y gastric bypass for morbid obesity, is it a problem?

Abstract: Background: Roux-en-Y gastric bypass (RYGB) can cause multiple food intolerances and gastrointestinal complaints are frequently reported after dairy consumption. We aimed to determine the prevalence of lactose malabsorption and intolerance, and complaints associated with dairy consumption in daily life, before and after RYGB. Method: The lactose breath test (LBT) and lactose tolerance test (LTT) was performed in 84 patients awaiting RYGB surgery and 84 patients after surgery. Gastrointestinal symptoms at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Decreased milk consumption after RYGB has also been reported in adults up to two years after surgery(22). The reason to decreased consumption was not investigated in the present study but others have found more frequently reported gastrointestinal complaints after dairy consumption in RYGB patients(23). The low consumption of milk is a concern in relation to previous findings reported from the present…”
supporting
confidence: 50%
“…Decreased milk consumption after RYGB has also been reported in adults up to two years after surgery(22). The reason to decreased consumption was not investigated in the present study but others have found more frequently reported gastrointestinal complaints after dairy consumption in RYGB patients(23). The low consumption of milk is a concern in relation to previous findings reported from the present…”
supporting
confidence: 50%
“…For instance, although eating more than 8 ounces a day of animal sources of protein (including lean ones) contributes to a lower REAP-S score, it is often recommended that pre-and post-bariatric patients consume foods or supplements rich in proteins over those rich in carbohydrates or fats to avoid protein deficiency and promote satiety [29][30][31]. Additional considerations should be made to other items that compose the REAP-S score, which can be of difficult adherence by patients both immediately following surgery as well as for long-term follow-up due to their reduced stomach capacity and common complaints about gastrointestinal issues [32]; however, that was not the immediate focus of this particular study.…”
Section: Discussionmentioning
confidence: 99%
“…Before surgery, 17.9% of patients showed positive results for lactose malabsorption. After surgery, 29.8% of patients showed positive results for lactose malabsorption [ 41 ]. Sendiny et al (2020) studied lactose malabsorption in patients that had not undergone bariatric treatments.…”
Section: Discussionmentioning
confidence: 99%
“…They compared 84 patients that were preparing for the RYGB procedure to 84 patients that had undergone the procedure. Lactose malabsorption was observed in 17.9% (N = 15) of patients before bariatric surgery and in 29.8% (N = 25) of patients after surgery [ 41 ].…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%